1999
DOI: 10.1074/jbc.274.42.29677
|View full text |Cite
|
Sign up to set email alerts
|

p53 Negatively Regulates cdc2 Transcription via the CCAAT-binding NF-Y Transcription Factor

Abstract: The p53 tumor suppressor protein regulates the transcription of regulatory genes involved in cell cycle arrest and apoptosis. We have reported previously that inducible expression of the p53 gene leads to the cell cycle arrest both at G 1 and G 2 /M in association with induction of p21 and reduction of mitotic cyclins (cyclin A and B) and cdc2 mRNA. In this study, we investigated the mechanism by which p53 regulates transcription of the cdc2 gene. Transient transfection analysis showed that wild type p53 repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 56 publications
13
147
0
Order By: Relevance
“…To examine whether p53 family proteins a ect to DNA binding activity of NF-Y, we performed a gel shift assay using CCAAT sequence that is found in the cdk1 promoter. NF-Y/DNA complex was detected as described previously (Yun et al, 1999). DNA binding activity of NF-Y was signi®cantly reduced by the expression of either p53, p63g, or p73b ( Figure 5).…”
Section: P53 Family Proteins Inactivate Dna Binding Activity Of Nf-y mentioning
confidence: 56%
See 2 more Smart Citations
“…To examine whether p53 family proteins a ect to DNA binding activity of NF-Y, we performed a gel shift assay using CCAAT sequence that is found in the cdk1 promoter. NF-Y/DNA complex was detected as described previously (Yun et al, 1999). DNA binding activity of NF-Y was signi®cantly reduced by the expression of either p53, p63g, or p73b ( Figure 5).…”
Section: P53 Family Proteins Inactivate Dna Binding Activity Of Nf-y mentioning
confidence: 56%
“…In addition to transcription activation, p53 has been shown to repress transcription of certain genes (Mack et al, 1993;Seto et al, 1992). We previously reported that p53 represses transcription of cdk1 and cyclin B1, both of whose transcriptions are regulated in a cell cycle dependent manner and irreversibly repressed in senescent cells (Yun et al, 1999;Park et al, 2000). Figure 4 shows that mRNA levels of cdk1 and cyclin B1 were signi®cantly reduced in cells expressing the isoforms of p63 or p73.…”
Section: Inducible Expression Of P63 Isoforms In P53-deficient Ej Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…One prominent example of a transactivated target gene is the cdk inhibitor p21 WAF1/CIP1 [6]. Other target genes such as several regulators of the G 2 /M checkpoint like cyclin B, cdc25C and cdk1 are repressed by p53 [7][8][9][10]. Many investigations concentrated on solving the mechanism of the p53-dependent repression without identifying one mechanism which would yield a general explanation for the regulatory details.…”
Section: Introductionmentioning
confidence: 99%
“…As control for activation and repression, pG13-lu (with 13 tandem wtp53-binding sites) and CDC2 promoter, cotransfected with wtp53, were used. wtp53 activated or repressed expression (el-Deiry et al, 1992;Yun et al, 1999) from pG13-lu or pCDC2-P-lu respectively ( Figure 1A1-2). Co-transfection of wtp53 with pM15-lu (with 15 tandem mutant p53-binding sites) or pGL2 showed very low activity ( Figure 1A1-2).…”
Section: Repression Of Expression Through Shp-1-p1 By Wtp53mentioning
confidence: 97%